Customer buying behavior intentions of internet service providers - the role of service quality and its aspects, satisfaction and value - Nikhashemi, Seyed Rajab; Paim, Laily; Osman, Syuhaily; Md Sidin, Samsinar (TextRoad Publication, 2013)
This study seeks to improve our understanding of Malaysian customer buying behaviour intention in mobile telecommunication industry by testing a conceptual model which has considered aspects of service quality, customer Satisfaction and customer perceived value towards buying behaviour simultaneously. The purposes of this study are to figure out the relationship among service quality, customer satisfaction and customer values on customer buying behaviour intention which could be one of the critical issues in Malaysian mobile telecommunication industry. However finding revealed that service quality, customer perceived value and customer satisfaction and their effects on customer buying behaviour in telecommunication Industry is rather divergent and related studies are fragmented especially for complicated interrelationship among them. Structure equation modeling and multiple regression analysis were applied to analyze the data. Data were collected from outlets of Maxis and DiGi which were located in Klang Valley area in Malaysia. The main findings of the study are as follow. (1) All service quality aspects has positive interrelationship with customer satisfaction and value (2) customer Satisfaction, service quality as well as customer perceived value positively affects customer buying behaviour.